Divergence of Mechanisms Regulating Respiratory Burst in Blood and Sputum Eosinophils and Neutrophils from Atopic Subjects - Lacy, Paige; Latif, Dalia Abdel; Steward, Melissa; Musat-Marcu, Sorin; Man, S. F. Paul; Moqbel, Redwan (The Journal of immunology (1950), 2003)
Eosinophil respiratory burst is an important event in asthma and related inflammatory disorders. However, little is known concerning activation of the respiratory burst NADPH oxidase in human eosinophils. Conversely, neutrophils are known to assemble NADPH oxidase in intracellular and plasma membranes. We hypothesized that eosinophils and neutrophils translocate NADPH oxidase to distinct intracellular locations, consistent with their respective functions in O2−-mediated cytotoxicity. PMA-induced O2– release assayed by cytochrome c was 3.4-fold higher in atopic human eosinophils than in neutrophils, although membrane-permeable dihydrorhodamine-123 showed similar amounts of release. Eosinophil O2– release was dependent on Rac, in that it was 54% inhibited by Clostridium difficile toxin B (400–800 ng/ml). In eosinophils stimulated with PMA, a pronounced shift of cytosolic Rac to p22phox-positive plasma membrane was observed by confocal microscopy, whereas neutrophils directed Rac2 mainly to intracellular sites coexpressing p22phox. Similarly, ex vivo sputum eosinophils from asthmatic subjects exhibited predominantly plasma membrane-associated immunoreactivity for Rac, whereas sputum neutrophils exhibited cytoplasmic Rac2 staining. Thus, activated sputum eosinophils, rather than neutrophils, may contribute significantly to the pathogenesis of asthma by extracellular release of tissue-damaging O2–. Our findings suggest that the differential modes of NADPH oxidase assembly in these cells may have important implications for oxidant-mediated tissue injury.